Severe asthma: what is new in the new millennium. Issue 2 (April 2020) - Ntontsi, Polyxeni; Samitas, Konstantinos; Zervas, Eleftherion; Gaga, Mina
Abstract : Purpose of review: Severe asthma remains a debilitating disease and a challenge for the clinicians. Novel therapies have been introduced and have greatly improved asthma control and more are under development or in clinical studies. These include anti-IL5/IL5R, anti-IL4/IL4R, anti IL13, anti- thymic stromal lymphopoietin (TSLP) and more, and severe asthma is currently managed in personalized medicine approach. However, there is still an unmet need to discover new, clinically available biomarkers and targeted therapies for a large group of severe asthma patients, particularly those with T2-low asthma. In this review, we briefly present the phenotypes and endotypes of severe asthma, the omics technologies in asthma as well as current and future treatments for both T2-high and T2-low asthma. Recent findings: In this review, we are going to present the effectiveness and safety of anti-IL5 therapies, the clinical trials for dupilumab and tezepelumab and the most significant molecules and biological agents used in trials as possible treatments forT2-low asthma. Summary: Novel anti-IL5 agents have changed the management of T2-high asthma resulting in improved disease control, QoL and lung function and importantly, fewer exacerbations. Nevertheless, there is still the need to find new treatments, particularly for T2-low asthma, which remains a challenge.